Crystal Ball Health Policies: A Case Against Preventive Testing For Alzheimer’s Disease - Inglese, Silvia; Lavazza, Andrea; Abbate, Carlo (Frontiers in Aging Neuroscience, 2022)
After the recent approval of a new drug for the treatment of Alzheimer's disease, the first in almost twenty years, it is useful to consider what are the real possibilities to make a preclinical diagnosis of dementia and to treat its symptoms. The scientific community widely agrees that the drugs available today can only slow down the progression of the disease; it therefore seems helpful to warn against encouraging the spread of preventive testing. In fact, faced with the prospect of drugs that promise to act in the first stage of Alzheimer's, there might be an incentive to invest in the research on biomarkers and even healthy adults could be encouraged to increasingly resort to such prediction tests. Our claim, however, is that such massive use of biomarkers would eventually make things worse for many individuals and for society as well. A few examples are given to illustrate this risk. Therefore, our proposal is to limit access to prediction testing until truly effective treatments for Alzheimer's are available.